A Representation of ISIS Rhetoric Concerning the Kurds: A Critical Discourse Analysis-based study - Abdalla, Shaho Burhan; Darweesh, Abdulrahman Kareem (Sulaimani Journal for Humanities, 2025)
Any political movement intends to seize power enforce certain political, social, economic and, occasionally, religious belief in a society. To achieve this, language plays a leading role. Thoughts and ideologies reside in language thus language has the power to control the way people think. Controlling people’s way of thinking implies controlling the way they behave in society. This has direct influence on social constructions and how realities are perceived in a certain society. Providing a brief history of the Islamic State of Iraq and Syria (ISIS) and the Kurds, this article aims to analyze a number of excerpts from the written discourse of ISIS to identify some of those beliefs and ideas hidden in their discourse concerning the Kurds, who are fighting against them in battlefields, based on Critical Discourse Analysis (CDA).